Shared-Care in Complex Malignant Hematology: An Integrative Review Using the RE-AIM Evaluation Framework. - Nixon, Shannon M.; Maze, Dawn C.; Parry, Monica; Mayo, Samantha J. (Current Oncology, 2024)
Complex malignant hematology (CMH) shared-care programs have been established to support patients with access to care closer to home. This integrative review examined what is known about CMH shared-care using the RE-AIM evaluation framework. We searched five electronic databases for articles published until 16 January 2024. Articles were included if they were qualitative or quantitative studies, reviews or discussion papers, and reported on an experience with shared-care (defined as a reciprocal, ongoing patient-sharing relationship between a specialist centre and community hospital) for patients with hematological malignancies, and examined one or more aspects of the RE-AIM framework. The search yielded 6523 articles; 10 articles describing eight shared-care experiences. Indicators of reach were reported for 65% of the programs, and emphasized some patient eligibility criteria. Effectiveness indicators were reported for 28% of programs, and suggested favourable survival outcomes within a shared-care model; however, health system impact and quality of life studies were lacking. Indicators of adoption and implementation were reported for 56% and 42% of programs, respectively, and emphasized multidisciplinary teams, infrastructure support, and communication strategies. Maintenance was not reported. Common elements contribute to the implementation of existing CMH shared-care programs; however, a formal evaluation remains an area of need.